PSYCHOLOGICAL AND PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF STUDENTS’ DIGITAL COMPETENCE - Svetlana Khamidovna Koneva; Luiza Salokhidinovna Latipova (Bright Mind Publishing, 2026)
In the context of the digital transformation of education, the issue of developing students’ digital competence as one of the key outcomes of the modern educational process becomes particularly relevant. Digital competence is considered as an integrative personal construct that includes knowledge, skills, abilities, value orientations, and experience in the use of digital technologies in educational, professional, and social activities.
Keywords: Digital competence, psychological and pedagogical conditions, digital educational environment, students, digital technologies.